Fish cell lines in aquaculture and biomedical research: A global perspective on development, repositories, and multidisciplinary applications - Anand Kumar; Bhartendu Vimal; Vikash Kumar; Sudeshna Sarker; Pushpa Kumari; Tapas Paul; Ajaya Kumar Rout; Ved Prakash Saini; Pramod Kumar Pandey; Bijay Kumar Behera; Anuj Tyagi (Molecular Biology Reports, 2026)

Amino Acid Biostimulants and Irrigation Impacts on Water Use Efficiency and Residual Water Management in Potato (Solanum tuberosum L.) Production - Vimal Kumar; Priyankar Raha; S. K. Tripathi; C. Patel; B. Kumar; D. K. Verma; A. K. Singh; D. R. Singh (Potato Research, 2026)

Intra-seasonal variability of coastal upwelling and its influence on plankton productivity along the southeastern Arabian Sea shelf during the summer monsoon - K.G. Vimal Kumar; K.B. Padmakumar; K.J. Jayalakshmi; Lathika Cicily Thomas; Shirin Jadhav; B.R. Smitha; V.N. Sanjeevan (Continental Shelf Research, 2026)

Uranium Assessment in Drinking Water: Techniques, Risks, and the Indian Context in a Global Framework - Jaswinder Kaur; Deep Shikha; Jatinder Garg; Thakur Sudesh Kumar Raunija; Vimal Mehta (Water, Air, & Soil Pollution, 2026)

Mesoscale eddy dynamics and their influence on biological productivity in the western Bay of Bengal during the fall intermonsoon - Vimal Kumar K.G.; Sajeev R; Smitha B.R; Jayalakshmi K.J.; J. K. Lix; S. Akash; Rasheed K; Sanjeevan V.N. (Environmental Monitoring and Assessment, 2026)

Fuzzy-Clustering Driven Soil Nutrients Management Zone Delineation in Mandarin (Citrus reticulata Blanco) Growing Areas of Malwa Plateau Region of India - Seema Bhardwaj; Sanjib Kumar Behera; Rahul Mishra; Sanjay Kumar Sharma; Sudhir Kumar Trivedi; Vimal Shukla; Akanksha Sikarwar; Arvind Kumar Shukla (Journal of Soil Science and Plant Nutrition, 2026)

Microplastic accumulation and risk assessment in shelf sediments of the coastal zone of Puducherry, India - Tejaswini Singh; Ankit Kumar Vimal; Spriha Yadav; Sundararajan Srinivasan; Sundarapandian Somaiah (Regional Studies in Marine Science, 2026)

Mineral–organic fertilization effects on productivity, soil carbon dynamics, and resilience in pearl millet–mustard–cowpea systems: Evidence from multi-year observations - Sunil Kumar; Dileep Kumar; Khushvadan C. Patel; Vimal J. Patel; Vinubhai P. Ramani; Ravi A. Patel; Sanjib K. Behera; Vijay Singh Meena; Bornali Borah (Field Crops Research, 2026)

Bisphenol-A (BPA) induces cytotoxicity and oxidative stress in gill cells of zebrafish (Danio rerio) - Anand Kumar; Bhartendu Vimal; Vikash Kumar; Sudeshna Sarker; Suvra Roy; Pushpa Kumari; Tapas Paul; Nikita Sahu; Ved Prakash Saini; Basanta Kumar Das (Aquatic Toxicology, 2026)

Exploring the oral microbiome: from traditional techniques to advanced omics and databases - Pankaj Kumar Arora; Mushtaq Ali; Aditya Pratap Singh; Vimal Kumar Dubey; Alok Srivastava; Sanjay Kumar Garg (Antonie van Leeuwenhoek, 2026)

Delineation of Soil Nutrient Management Zone for Site-Specific Sulphur and Micronutrient Management: A Case Study of Jhansi Bundelkhand Region of India - Rahul Mishra; Sanjib Kumar Behera; Arvind Kumar Shukla; Vimal Shukla (Agricultural Research, 2026)

Biochar-based green nickel catalyst from Persea americana seed waste: a sustainable approach to supported metal catalysis - Sewunet Abebayehu; Jabasingh S. Anuradha; Anteneh Marelign; Vimal Katiyar; Manoj Kumar Dhal; Shegaw Ahmed Mohammed (Biodegradation, 2026)

Infection-associated Opsoclonus: A Systematic Review - Ravindra Kumar Garg; Amita Jain; Shweta Pandey; Vimal Paliwal; Vinay Suresh; Sanjay Singhal (The Cerebellum, 2026)

Unveiling stagnant flooding tolerance in lowland NERICAs: genomic insights and breeding prospects - Vimal Kumar Semwal; Shittu Afeez; Olatunde A. Bhadmus; Okanlawon Jolayemi; Ramaiah Venuprasad (Theoretical and Applied Genetics, 2026)

Ginsenosides for Multi-target Intervention in Alzheimer’s Disease: Current Evidence, Challenges, and Future Directions - Ghaleb Oriquat; Afaq Mahdi Ali; Malathi H.; Israa Abdulhameed Ahmad; Laxmidhar Maharana; Ashish Singh Chauhan; Vimal Arora; Bilakshan Purohit; Manoj Kumar-Mishra (Molecular Neurobiology, 2026)

Extracellular Protein Quality Control in Tau Pathology - Prasun Kumar Bhunia; Deepanshu Verma; Priyanka Vimal; Prasad Kasturi (Molecular Neurobiology, 2026)

Eco-engineered N-Methyl-2-pyrrolidone-free antibacterial chitosan/cellulose acetate membrane separator for real hospital wastewater-fed microbial fuel cells - Aparajita Roy; Sonu Kumar; Bhanupriya Das; Kuhelika Das; Amit Kumar; Akio Ebihara; Chin Tsan Wang; Vimal Katiyar (Next Research, 2025)

Optimizing Marketable Tuber Production in Potato (Solanum tuberosum L.) with Irrigation and Biostimulants Application - Vimal Kumar; Priyankar Raha; Chandrabhan Patel; D. K. Verma; Anshuman Kohli; A. K. Singh; D. R. Singh (Potato Research, 2025)

From ocean to opportunity: Upcycling fishing net waste into high-performance, reprocessable nylons - S. Vimal Kumar; B.D.S. Deeraj; Siddhesh Sadashiv Rege; A. Moulishwar Reddy; S. Ram Prasanth; Sk Safikul Islam; Indranil Dey; Ketaki Samanta; Ashok Misra; Suryasarathi Bose (Chemical Engineering Journal, 2025)

A critical review on advancing bioinspired smart membranes for green energy recovery in microbial fuel cells: Paving the way for a sustainable future - Aparajita Roy; Amit Kumar; Akio Ebihara; Chin Tsan Wang; Vimal Katiyar (Journal of Environmental Chemical Engineering, 2025)

Bioanalytical Method Development, Pharmacokinetic Determination, and Time-Dependent Mobility of a Novel Chronosystem of ACE Inhibitor - Saniya Jawed; Satish CS; Vimal Kumar (Journal of Pharmaceutical Innovation, 2025)

Quantification of soil erosion in mountain catchment in the Himalaya using meteoric 10Be as a tracer tool - Arkaprabha Sarkar; Vimal Singh; Pankaj Kumar; Pavitra Kumar; Rajveer Sharma (Journal of Mountain Science, 2025)

Prakuam: Local knowledge commodification and preservation of Khmer silverware techniques and objects in Surin Province of Thailand - Suriya Klangrit; Vimal Kumar; Tzu-Chuen Lu; David D. Perrodin (The Extractive Industries and Society, 2025)

Geostatistics-Based Understanding of Temporal Changes In Spatial Distribution of Soil Fertility Parameters In An Intensively Cultivated Area of North India - Sanjib Kumar Behera; Arvind Kumar Shukla; Rohtas Kumar; Rahul Mishra; Vimal Shukla; Harendra Yadav; Siba Prasad Datta (Journal of Soil Science and Plant Nutrition, 2025)

Development and characterization of polyvinyl alcohol/gelatin/chitosan hydrogel for tissue engineering and wound healing applications using a fish cell line model - Sivaraj Mithra; Ali Asna Jabeen; Vinay Kumar; Seepoo Abdul Majeed; Manickam Balu Balaji; Sugumar Vimal; Dawood Mubeen Sultana; Sakvai Mohammed Safiullah; Gani Taju; Azeez Sait Sahul Hameed (In Vitro Cellular & Developmental Biology - Animal, 2025)

Impacts of faulty grey infrastructures on the bathymetry and salinity of Vembanad Lake, a tropical estuary along the south west coast of India - Vimal Kumar K. G.; Sanjeevan V. N. (Environmental Monitoring and Assessment, 2025)

Oxidative pyrolysis of alkali lignin using nitrogen functionalized graphene oxide-cerium oxide nanocatalysts: Mechanistic insights thorough density functional theory - Shivam Kumar; Pankaj Kumar; Navneet Kumar; Jinsub Park; Vimal Chandra Srivastava (Bioresource Technology, 2025)

The conformational preference of dynamic crosslinker modulates the ‘closed-loop’ circular economy in polypropylene vitrimer - Indranil Dey; Ketaki Samanta; Sayon Ghosh; Tanay Debnath; Samir Mandal; Siddhesh Sadashiv Rege; S. Vimal Kumar; Sk. Safikul Islam; Ashok Misra; Suryasarathi Bose (Chemical Engineering Journal, 2025)

Structure-based drug designing for potential antiviral activity of selected natural product against Monkeypox (Mpox) virus and its host targets - Vimal K. Maurya; Swatantra Kumar; Shivani Maurya; Saniya Ansari; Janusz T. Paweska; Ahmed S. Abdel-Moneim; Shailendra K. Saxena (VirusDisease, 2024)

Novel 2-[(8-hydroxyquinolin-7-yl)(phenyl)methylamino]benzoic acid analogs targeting the active site of botulinum neurotoxins: designing, synthesis, and biological evaluation - Surabhi Agnihotri; Vinita Chauhan Kushwah; Surabhi Bansal; Manorama Vimal; Nandita Saxena; Ram Kumar Dhaked (Medicinal Chemistry Research, 2024)

Microwave Synthesis of Fluorescent Carbon Quantum dots from Araucaria Heterophylla Gum: Application in Drug Detection - Rohitash Kumar; Vimal K. Bhardwaj (Journal of Fluorescence, 2024)

PCA and fuzzy clustering-based delineation of soil nutrient (S, B, Zn, Mn, Fe, and Cu) management zones of sub-tropical Northeastern India for precision nutrient management - Arvind Kumar Shukla; Sanjib Kumar Behera; Anjali Basumatary; Indira Sarangthem; Rahul Mishra; Samiron Dutta; Yogesh Sikaniya; Akanksha Sikarwar; Vimal Shukla; Siba Prasad Datta (Journal of Environmental Management, 2024)

Landfill-mined soil-like fraction (LMSF) use in biopolymer composting: Material pre-treatment, bioaugmentation and agricultural prospects - Arnab Banerjee; Manoj Kumar Dhal; Kshitij Madhu; Charakho N. Chah; Bharat Rattan; Vimal Katiyar; Sreedeep Sekharan; Ajit K. Sarmah (Environmental Pollution, 2024)

Hazard identification of endocrine-disrupting carcinogens (EDCs) in relation to cancers in humans - Neha Sharma; Vinay Kumar; Vimal S.; Mridul Umesh; Preeti Sharma; Basheer Thazeem; Komalpreet Kaur; Jithin Thomas; Ritu Pasrija; Divya Utreja (Environmental Toxicology and Pharmacology, 2024)

Multi-objective artificial bee colony algorithm for reducing carbon emission and maximizing profit in a circular supply chain network - Aravind Raj Sakthivel; K. E. K. Vimal; Jayakrishna Kandasamy; S. N. Shiva; Gideon Jayanth; A. Shanmuga Nishanth; D. Vignesh Kumar (Environment, Development and Sustainability, 2024)

Microenvironment of Landfill-Mined Soil-Like Fractions (LMSF): Evaluating the Polymer Composting Potential Using Metagenomics and Geoenvironmental Characterization - Arnab Banerjee; Charakho N. Chah; Manoj Kumar Dhal; Kshitij Madhu; Kiran Vilas Dhobale; Bharat Rattan; Vimal Katiyar; Sreedeep Sekharan (International Journal of Environmental Research, 2024)

Recent advances in nanotechnology-based modifications of micro/nano PET plastics for green energy applications - J.R. Anusha; T. Citarasu; G. Uma; S. Vimal; Chinnaperumal Kamaraj; Vinay Kumar; Khursheed Muzammil; M. Mani Sankar (Chemosphere, 2024)

Effect of waste Dunaliella tertiolecta biomass ethanolic extract and turmeric essential oil on properties of guar gum-based active films - Kona Mondal; Sayan Kumar Bhattacharjee; Vaibhav V. Goud; Vimal Katiyar (Food Hydrocolloids, 2024)

Algae-based approaches for Holistic wastewater management: A low-cost paradigm - Simranjeet Singh; Lav Singh; Vijay Kumar; Wahid Ali; Praveen C. Ramamurthy; Daljeet Singh Dhanjal; Nikhita Sivaram; Ruby Angurana; Joginder Singh; Vimal Chandra Pandey; Nadeem A. Khan (Chemosphere, 2023)

Studies on natural regeneration, floristic composition, biomass, carbon density and soil properties along an altitudinal gradient in the north-western Himalayas, India - Ghanshyam Singh; Vimal Chauhan; C.L. Thakur; M.L. Verma; Rohit Bishist; Prem Prakash; Krishan Lal Gautam; Harish Sharma; Rushal Dogra; Kamal Kishore; Munesh Kumar (Forest Ecology and Management, 2023)

Photocatalytic behaviors of bismuth-based mixed oxides: Types, fabrication techniques and mineralization mechanism of antibiotics - Vikas Thakur; Seema Singh; Praveen Kumar; Sameeksha Rawat; Vimal Chandra Srivastava; Shang-Lien Lo; Urška Lavrenčič Štangar (Chemical Engineering Journal, 2023)

Plant -microbe assisted emerging contaminants (ECs) removal and carbon cycling - Anand Giri; Deepak Pant; Vimal Chandra Srivastava; Manoj Kumar; Ashok Kumar; Meera Goswami (Bioresource Technology, 2023)

Corrigendum to “Plant diversity and ecological potential of naturally colonizing vegetation for ecorestoration of fly ash disposal area” [Ecological Engineering 176 (2022) 106533] - Swati Yadav; Vimal Chandra Pandey; Munesh Kumar; Lal Singh (Ecological Engineering, 2023)

Nanostructured coating strategies of cathode for improved sodium ion battery performance - Vimal K. Tiwari; Rajendra Kumar Singh (Chemical Engineering Journal, 2023)

Synthesis of bio-based materials from agricultural residues for treatment of petrochemical wastewater - Mohammad Nasir; Praveen Kumar; Vimal Chandra Srivastava; Shilpi Verma; Ramanpreet Kaur; Indra Deo Mall; Urška Lavrenčič Štangar (Clean Technologies and Environmental Policy, 2023)
4-Carboxybenzaldehyde (4-CBA), a major component of purified terephthalic acid wastewater, is toxic to living organisms and required to be removed before the discharge of treated wastewater in a natural water body. In this work, the adsorptive removal of 4-CBA was studied using bagasse fly ash (BFA), a waste product from the sugar industry. The adsorption capacity of BFA was compared with the commercially available adsorbent, granular activated carbon (GAC). A 4-factorial, 5-stage central composite design (CCD) was used to optimize 4-CBA removal and adsorption uptake by BFA using response surface methodology (RSM). The variables considered for the study were pH, adsorbent dose ( m ), initial concentration ( C o ) and time ( t ). At the optimum treatment conditions of pH = 4, m = 9 g/L, C o = 100 mg/L and t = 7.5 h, the removal efficiency and adsorption uptake of 4-CBA on BFA were found to be 79% and 9.9 mg/g, respectively. BET surface area of BFA was determined to be 284 m 2 /g. A kinetic study was performed using a first- and second pseudo-order model. The adsorption equilibrium data were fitted for various adsorption models. A positive value $$Δ H^{0}$$ Δ H 0 indicates that the adsorption process is endothermic. This study indicated that BFA is a cost-effective adsorbent for the removal of 4-CBA with high adsorption capacity and fast kinetics. Graphical Abstract

Hepato and renoprotective activity of Kappaphycus alvarezii ethanolic extract in cisplatin causes hepatic and kidney harm in Albino Wistar rats - Annamalai Natarajan; Radhakrishnan Prabakarakrishnan; Kasivelu Govindaraju; Vimal Sugumar; Kuppusamy Sathiskumar; Jayaraman Narenkumar; Aadhikesavan Ramanan; Balasubramanian Senthil Kumar (Aquaculture International, 2023)

Investigating the recovery in ecosystem functions and multifunctionality after 10 years of natural revegetation on fly ash technosol - Ashutosh Kumar Singh; Xiai Zhu; Chunfeng Chen; Bin Yang; Vimal Chandra Pandey; Wenjie Liu; Nandita Singh (Science of The Total Environment, 2023)

Catalytic oxidation of Bisphenol A with Co3+ rich spinel Co3O4: Performance evaluation with peroxymonosulfate activation and mineralization mechanism - Seema Singh; Praveen Kumar; Ritesh Patidar; Vimal Chandra Srivastava; Shang-Lien Lo; Urška Lavrenčič Štangar (Journal of Environmental Chemical Engineering, 2023)

Spatio-temporal variability of available sulphur and micronutrients (Zn, Fe, Cu, Mn, B and Mo) in soils of a hilly region of northern India - Sanjib Kumar Behera; Arvind Kumar Shukla; Satya Pratap Pachauri; Vimal Shukla; Yogesh Sikaniya; Prakash Chandra Srivastava (CATENA, 2023)

Peroxymonosulfate activation with an α-MnO2/Mn2O3/Mn3O4 hybrid system: parametric optimization and oxidative degradation of organic dye - Seema Singh; Ritesh Patidar; Vimal Chandra Srivastava; Qicheng Qiao; Praveen Kumar; Ajay Singh; Shang-Lien Lo (Environmental Science and Pollution Research, 2023)

Environment and economic analysis of reverse supply chain scenarios for remanufacturing using discrete-event simulation approach - Mahadharsan Ravichandran; K. E. K. Vimal; Vikas Kumar; Onkar Kulkarni; Sundaramali Govindaswamy; Jayakrishna Kandasamy (Environment, Development and Sustainability, 2023)

Seedling growth and physicochemical transformations of rice nursery soil under varying levels of coal fly ash and vermicompost amendment - Sanat Kumar Dwibedi; Sanjat Kumar Sahu; Vimal Chandra Pandey; Kumbha Karna Rout; Manorama Behera (Environmental Geochemistry and Health, 2023)

Designing, synthesis and evaluation of derived analogues of selected small molecule non-peptidic inhibitors against serotype BoNT/ F - Ritika Chauhan; Vinita Chauhan Kushwah; Surabhi Agnihotri; Manorama Vimal; Nandita Saxena; Ram Kumar Dhaked (Toxicon, 2023)

An Indigenous, Field-Deployable, Lateral Flow Immunochromatographic Assay Rapidly Detects Infectious Myonecrosis in Shrimp, Litopenaeus vannamei - S. Santhosh Kumar; Snehal Jamalpure; A. Nafeez Ahmed; G. Taju; S. Vimal; S. Abdul Majeed; S. Suryakodi; Syed Rahamathulla; Kishore M. Paknikar; Jyutika M. Rajwade; A. S. Sahul Hameed (Marine Biotechnology, 2022)

Optimized Production of Medically Significant Enzyme L-Asparaginase Under Submerged and Solid-State Fermentation From Agricultural Wastes - Archana Vimal; Awanish Kumar (Current Microbiology, 2022)

Design, synthesis, in vivo and in silico evaluation of novel benzothiazole-hydrazone derivatives as new antiepileptic agents - Himanshu Singh; Rajnish Kumar; Avijit Mazumder; Salahuddin; Ranjeet Kumar Yadav; Bharti Chauhan; Vimal Datt; Km Shabana; Mohd. Mustaqeem Abdullah (Medicinal Chemistry Research, 2022)

Effect of fly ash and vermicompost amendment on rhizospheric earthworm and nematode count and change in soil carbon pool of rice nursery - Sanat Kumar Dwibedi; Sanjat Kumar Sahu; Vimal Chandra Pandey; Jayanta Kumar Mahalik; Manorama Behera (Environmental Science and Pollution Research, 2022)

Biopolymer-based nanocomposite films and coatings: recent advances in shelf-life improvement of fruits and vegetables - Indra Bhusan Basumatary; Avik Mukherjee; Vimal Katiyar; Santosh Kumar (Critical Reviews in Food Science and Nutrition, 2022)

Differential response of Bay of Bengal during deficit and normal monsoons - K. J. Jayalakshmi; B. R. Smitha; V. N. Sanjeevan; K. G. Vimal Kumar (Environmental Monitoring and Assessment, 2022)

Pyrrolo[2,1-f][1,2,4]triazine: a promising fused heterocycle to target kinases in cancer therapy - Sarbjit Singh; Divya Utreja; Vimal Kumar (Medicinal Chemistry Research, 2022)

Neurodegenerative Disorders of Alzheimer, Parkinsonism, Amyotrophic Lateral Sclerosis and Multiple Sclerosis: An Early Diagnostic Approach for Precision Treatment - Nishit Pathak; Sunil Kumar Vimal; Ishi Tandon; Lokesh Agrawal; Cao Hongyi; Sanjib Bhattacharyya (Metabolic Brain Disease, 2022)

Serum fractalkine and 3-nitrotyrosine levels correlate with disease severity in Parkinson’s disease: a pilot study - Manjeet Gupta; Vimal Kumar Paliwal; G. Nagesh Babu (Metabolic Brain Disease, 2022)

l-asparaginase: Need for an Expedition from an Enzymatic Molecule to Antimicrobial Drug - Archana Vimal; Awanish Kumar (International Journal of Peptide Research and Therapeutics, 2022)

Development and characterization of five novel cell lines from snubnose pompano, Trachinotus blochii (Lacepede, 1801), and their application in gene expression and virological studies - Nafeez Ahmed Abdul; Abdul Majeed Seepoo; Taju Gani; Vimal Sugumar; Suryakodi Selvam; Badhusha Allahbagash; Abdul Nazar Abdul kuthoos; Ramesh Kumar Palsamy; Paknikar Kishore M.; Jyutika M. Rajwade; Sait Sahul Hameed Azeez (Journal of Fish Diseases, 2022)
Five novel permanent cell lines have been established from gill, heart, kidney, eye and fin of snubnose pompano, Trachinotus blochii . They were designated as snubnose pompano gill (SPG), snubnose pompano heart (SPH), snubnose pompano kidney (SPK), snubnose pompano eye (SPE) and snubnose pompano fin (SPF), respectively. All these cell lines were characterized and cryopreserved successfully at different passage levels. Cell lines were passaged every alternate day; SPG, SPH, SPK, SPE and SPF cell lines attained passage levels of 68, 74, 82, 79 and 106, respectively, since the initiation of their development in 2019. The cell lines grew well in Leibovitz's 15 medium containing 15% foetal bovine serum at 28°C. Immunophenotyping of the cell lines revealed the presence of fibronectin and pancytokeratin. No mycoplasma contamination was found. The transfection study revealed the gene expression efficiency of these cell lines by expressing the green fluorescent protein (GFP). The authentication on origin of cell lines from T. blochii was confirmed by amplification of species‐specific mitochondrial cytochrome oxidase I gene. The results showed the susceptibility of these cell lines to fish nodavirus (FNV) and tilapia lake virus (TiLV) and resistance to cyprinid herpesvirus 2 (CyHV‐2). The FNV infection in the cell lines was confirmed by RT‐PCR, Western blot, ELISA and immunocytochemistry, while TiLV infection was confirmed by RT‐PCR assay. These results revealed that these cell lines are suitable for virological and foreign gene expression studies.

Potential and safe utilization of Fly ash as fertilizer for Pisum sativum L. Grown in phytoremediated and non-phytoremediated amendments - Tanushree Bhattacharya; Shikha Kumari Pandey; Vimal Chandra Pandey; Abhishek Kumar (Environmental Science and Pollution Research, 2021)

Ecological restoration of coal fly ash–dumped area through bamboo plantation - Raushan Kumar; Mohan Manu Thangaraju; Manoj Kumar; Sanjog Tarachand Thul; Vimal Chandra Pandey; Swati Yadav; Lal Singh; Sunil Kumar (Environmental Science and Pollution Research, 2021)

In vitro propagation of infectious myonecrosis virus in C6/36 mosquito cell line - S. Santhosh Kumar; S. Sivakumar; S. Abdul Majeed; S. Vimal; G. Taju; A. S. Sahul Hameed (Journal of Fish Diseases, 2021)
Infectious myonecrosis (IMN) is an important shrimp viral disease caused by infectious myonecrosis virus (IMNV). Based on previous reports, an attempt was made to propagate IMNV in apparently healthy C6/36 subclone of Aedes albopictus cell line. The confirmatory assays such as RT‐PCR, real‐time PCR and bioassay revealed that C6/36 cells were found to be susceptible to IMNV and these cells could be used easily for isolation and propagation of IMNV. The results of real‐time PCR assay showed that a lower C T value of 22.25 in IMNV‐infected cells was obtained on 10 day post‐infection (d p.i.), whereas the higher C T value of 35.21 was obtained in IMNV‐infected cells on 2 d p.i. There is no significant difference between C T values of IMNV production in vitro using C6/36 cell line and in vivo using shrimp. The IMNV propagated in C6/36 cells is capable of infecting shrimp and caused 100% mortality in shrimp. Clinical signs observed in shrimp injected with IMNV propagated in C6/36 cell line were found to be similar to naturally infected shrimp.

Evolutionary Algorithm based Ensemble Extractive Summarization for Developing Smart Medical System - Chirantana Mallick; Asit Kumar Das; Janmenjoy Nayak; Danilo Pelusi; S. Vimal (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Butea monosperma: a leguminous species for sustainable forestry programmes - Apurva Rai; Vimal Chandra Pandey; Ashutosh Kumar Singh; Nandita Ghoshal; Nandita Singh (Environment, Development and Sustainability, 2021)

Silencing of prophenoloxidase (proPO) gene in freshwater prawn, Macrobrachium rosenbergii, makes them susceptible to white spot syndrome virus (WSSV) - S. Thamizhvanan; A. Nafeez Ahmed; D. Vinoth Kumar; S. Vimal; S. Abdul Majeed; G. Taju; Chris Hauton; A. S. Sahul Hameed (Journal of Fish Diseases, 2021)
Prophenoloxidase (proPO) is very important to protect the invertebrates from microbial infections. Our previous studies revealed that proPO was up‐regulated in WSSV‐injected Macrobrachium rosenbergii and is responsible for protecting M. rosenbergii from WSSV. In order to prove this mechanism, an attempt was made in the present study to silence the proPO gene in freshwater prawn by injection of dsRNA‐proPO followed by WSSV challenge. Two partial fragments of proPO with the size of 251 and 331 bp were used to synthesize dsRNA using LITMUS38i vector and E. coli . The bacterially synthesized dsRNA‐proPO was used to silence proPO gene to determine its involvement in developing resistance in prawn against WSSV. In proPO gene‐silenced prawn, 100% mortality was observed after WSSV challenge whereas no mortality was observed in prawn injected with WSSV alone. The WSSV infection in gene‐silenced prawn was confirmed by PCR, and its propagation was quantified by ELISA and real‐time PCR at different time intervals. Real‐time PCR assay revealed a significant reduction in the expression of proPO gene in WSSV‐challenged proPO‐silenced prawn when compared to normal prawn. Level of proPO was reduced significantly in the haemolymph of proPO‐silenced prawn when compared to prawn injected with PBS.

Induced secretion system mutation alters rhizosphere bacterial composition in Sorghum bicolor (L.) Moench - Vimal Kumar Balasubramanian; Lavanya Dampanaboina; Christopher Joseph Cobos; Ning Yuan; Zhanguo Xin; Venugopal Mendu (Planta, 2021)
Main conclusion A novel inducible secretion system mutation in Sorghum named Red root has been identified. The mutant plant root exudes pigmented compounds that enriches Actinobacteria in its rhizosphere compared to BTx623. Abstract Favorable plant–microbe interactions in the rhizosphere positively influence plant growth and stress tolerance. Sorghum bicolor , a staple biomass and food crop, has been shown to selectively recruit Gram-positive bacteria (Actinobacteria) in its rhizosphere under drought conditions to enhance stress tolerance. However, the genetic/biochemical mechanism underlying the selective enrichment of specific microbial phyla in the sorghum rhizosphere is poorly known due to the lack of available mutants with altered root secretion systems. Using a subset of sorghum ethyl methanesulfonate (EMS) mutant lines, we have isolated a novel Red root ( RR ) mutant with an increased accumulation and secretion of phenolic compounds in roots. Genetic analysis showed that RR is a single dominant mutation. We further investigated the effect of root-specific phenolic compounds on rhizosphere microbiome composition under well-watered and water-deficit conditions. The microbiome diversity analysis of the RR rhizosphere showed that Actinobacteria were enriched significantly under the well-watered condition but showed no significant change under the water-deficit condition. BTx623 rhizosphere showed a significant increase in Actinobacteria under the water-deficit condition. Overall, the rhizosphere of RR genotype retained a higher bacterial diversity and richness relative to the rhizosphere of BTx623, especially under water-deficit condition. Therefore, the RR mutant provides an excellent genetic resource for rhizosphere-microbiome interaction studies as well as to develop drought-tolerant lines. Identification of the RR gene and the molecular mechanism through which the mutant selectively enriches microbial populations in the rhizosphere will be useful in designing strategies for improving sorghum productivity and stress tolerance.

Description on variability of shelf-edge hydrography and current structure of the South Eastern Arabian Sea during summer and winter monsoons - K. G. Vimal Kumar; K. Rasheed; B. R. Smitha; S. Vishnu Narayanan Nampoothiri; M. Sudhakar (Environmental Monitoring and Assessment, 2020)

Enhanced oxidative stress, damage and inadequate antioxidant defense contributes towards insufficient recovery in water deficit stress and heat stress combination compared to either stresses alone in Chenopodium album (Bathua) - Vimal Kumar Semwal; Renu Khanna-Chopra (Physiology and Molecular Biology of Plants, 2020)

Structure-based drug designing for potential antiviral activity of selected natural products from Ayurveda against SARS-CoV-2 spike glycoprotein and its cellular receptor - Vimal K. Maurya; Swatantra Kumar; Anil K. Prasad; Madan L. B. Bhatt; Shailendra K. Saxena (VirusDisease, 2020)

Structural, glycosylation and antigenic variation between 2019 novel coronavirus (2019-nCoV) and SARS coronavirus (SARS-CoV) - Swatantra Kumar; Vimal K. Maurya; Anil K. Prasad; Madan L. B. Bhatt; Shailendra K. Saxena (VirusDisease, 2020)

In vitro propagation of tilapia lake virus in cell lines developed from Oreochromis mossambicus - Ravi Nanthini; Seepoo Abdul Majeed; Sugumar Vimal; Gani Taju; Selvam Sivakumar; Shanmugam Santhosh Kumar; Devika Pillai; Kalasseril Girijan Sneha; Chakalaparambil Gokulan Rakesh; Azeez Sait Sahul Hameed (Journal of Fish Diseases, 2019)
Tilapia lake virus (TiLV)‐suspected samples of tilapia were collected from grow‐out ponds located with clinical signs and mortality ranged from 5% to 50%. The reverse transcription–polymerase chain reaction (RT‐PCR) assay revealed the presence of TiLV in the disease outbreak ponds. Cell lines were developed from heart, gill and eye of Mozambique tilapia and characterized. Morphologically, these cell lines are composed of epithelioid cells. The optimum growth of these cells was observed at 28°C and 20% concentration of FBS. After cryopreservation, 70%–90% of cells were found to be viable. The cells of all three cell lines were found to be positive to fibronectin and pancytokeratin. PCR amplification of 16S rRNA and COI of O. mossambicus confirmed the origin of these cell lines from O. mossambicus . Heart and gill cell lines were found to be highly susceptible to TiLV and found to be useful for its isolation from infected fish samples. The experimental infection was carried out in O. niloticus and O. mossambicus using the TiLV propagated in susceptible cell lines. The RT‐PCR results revealed the presence of TiLV in brain, gill, liver, kidney, spleen, eye, muscle, intestine and heart of experimentally infected O. niloticus and O. mossambicus .

Inhibitors of CPH1-MAP Kinase Pathway: Ascertaining Potential Ligands as Multi-Target Drug Candidate in Candida albicans - Anubhuti Jha; Archana Vimal; Afroz Bakht; Awanish Kumar (International Journal of Peptide Research and Therapeutics, 2019)

Multiple infections caused by white spot syndrome virus and Enterocytozoon hepatopenaei in pond‐reared Penaeus vannamei in India and multiplex PCR for their simultaneous detection - S. Thamizhvanan; S. Sivakumar; S. Santhosh Kumar; D. Vinoth Kumar; S. Suryakodi; K. Balaji; T. Rajkumar; S. Vimal; S. Abdul Majeed; G. Taju; A. S. Sahul Hameed (Journal of Fish Diseases, 2019)
White leg shrimp, Penaeus vannamei , were collected on a monthly basis from grow‐out ponds located at Tamil Nadu and Andhra Pradesh states along the east coast of India for screening of viral and other pathogens. Totally 240 shrimp samples randomly collected from 92 farms were screened for white spot syndrome virus (WSSV), infectious hypodermal and haematopoietic necrosis virus (IHHNV), infectious myonecrosis virus (IMNV) and Enterocytozoon hepatopenaei (EHP). The number of shrimp collected from shrimp farms ranged from 6 to 20 based on the body weight of the shrimp. All the shrimp collected from one farm were pooled together for screening for pathogens by PCR assay. Among the samples screened, 28 samples were WSSV‐positive, one positive for IHHNV and 30 samples positive for EHP. Among the positive samples, four samples were found to be positive for both WSSV and EHP, which indicated that the shrimp had multiple infections with WSSV and EHP. This is the first report on the occurrence of multiple infections caused by WSSV and EHP. Multiplex PCR (m‐PCR) protocol was standardized to detect both pathogens simultaneously in single reaction instead of carrying out separate PCR for both pathogens. Using m‐PCR assay, naturally infected shrimp samples collected from field showed two prominent bands of 615 and 510 bp for WSSV and EHP, respectively.

Reproductive sink enhanced drought induced senescence in wheat fertile line is associated with loss of antioxidant competence compared to its CMS line - Vimal Kumar Semwal; Renu Khanna-Chopra (Physiology and Molecular Biology of Plants, 2018)

A new strain of white spot syndrome virus affecting Litopenaeus vannamei in Indian shrimp farms - S Sivakumar; S Vimal; S Abdul Majeed; S Santhosh Kumar; G Taju; N Madan; T Rajkumar; S Thamizhvanan; K V Shamsudheen; V Scaria; S Sivasubbu; A S Sahul Hameed (Journal of Fish Diseases, 2018)
White spot syndrome virus ( WSSV )‐infected shrimp samples collected from grow‐out ponds located at Nellore, Andhra Pradesh, India, showed WSSV negative and positive by PCR using primer sets specific to ORF 119 and VP 28 gene of WSSV , respectively. This indicated the deletion of genetic fragments in the genome of WSSV . The WSSV isolate along with lab strain of WSSV was subjected to next‐generation sequencing. The sequence analysis revealed a deletion of 13,170 bp at five positions in the genome of WSSV ‐ NS (new strain) relative to WSSV ‐ TH and WSSV ‐ LS (lab strain). The PCR analysis using the ORF 's specific primer sets revealed the complete deletion of 10 ORF s in the genome of WSSV ‐ NS strain. The primer set was designed based on sequence covering ORF 161/162/163 to amplify a product of 2,748 bp for WSSV ‐ LS and 402 bp for WSSV ‐ NS . Our surveillance programme carried out since 2002 revealed the replacement of WSSV ‐ LS by WSSV ‐ NS in Indian shrimp culture system.

Mutational analyses of regulatory genes, mexR, nalC, nalD and mexZ of mexAB-oprM and mexXY operons, in efflux pump hyperexpressing multidrug-resistant clinical isolates of Pseudomonas aeruginosa - Manju Suresh; N. Nithya; P. R. Jayasree; K. P. Vimal; P. R. Manish Kumar (World Journal of Microbiology and Biotechnology, 2018)

Multimodel assessment of sensitivity and uncertainty of evapotranspiration and a proxy for available water resources under climate change - Vimal Mishra; Rohini Kumar; Harsh L. Shah; Luis Samaniego; S. Eisner; Tao Yang (Climatic Change, 2017)

Development of fast and robust multiresidual LC-MS/MS method for determination of pharmaceuticals in soils - Oksana Golovko; Olga Koba; Radka Kodesova; Ganna Fedorova; Vimal Kumar; Roman Grabic (Environmental Science and Pollution Research, 2016)

GC/MS profiling, in vitro anti-leptospiral and haemolytic activities of Boesenbergia rotunda (L.) Mansf. used as a medicinal plant by Nicobarese of Andaman and Nicobar Islands - M. Punnam Chander; K. Vinod Kumar; Chandan Lall; R. Vimal Raj; P. Vijayachari (Natural Product Research, 2016)

Adsorptive desulfurization by zinc-impregnated activated carbon: characterization, kinetics, isotherms, and thermodynamic modeling - Sandeep Kumar Thaligari; Vimal Chandra Srivastava; Basheswar Prasad (Clean Technologies and Environmental Policy, 2016)

Status and Interrelationship of Zinc, Copper, Iron, Calcium and Selenium in Prostate Cancer - Bhupendra Pal Singh; Shailendra Dwivedi; Urmila Dhakad; Ramesh Chandra Murthy; Vimal Kumar Choubey; Apul Goel; Satya Narayan Sankhwar (Indian Journal of Clinical Biochemistry, 2016)

Genomic regions and underlying candidate genes associated with coleoptile length under deep sowing conditions in a wheat RIL population - Kalpana Singh; Sanyukta Shukla; Suhas Kadam; Vimal Kumar Semwal; Nagendra Kumar Singh; Renu Khanna-Chopra (Journal of Plant Biochemistry and Biotechnology, 2015)

Evaluating wind extremes in CMIP5 climate models - Devashish Kumar; Vimal Mishra; Auroop R. Ganguly (Climate Dynamics, 2015)

Phytodiversity on fly ash deposits: evaluation of naturally colonized species for sustainable phytorestoration - Vimal Chandra Pandey; Prem Prakash; Omesh Bajpai; Akhilesh Kumar; Nandita Singh (Environmental Science and Pollution Research, 2015)

Removal and seasonal variability of selected analgesics/anti-inflammatory, anti-hypertensive/cardiovascular pharmaceuticals and UV filters in wastewater treatment plant - Oksana Golovko; Vimal Kumar; Ganna Fedorova; Tomas Randak; Roman Grabic (Environmental Science and Pollution Research, 2014)

Delayed expression of SAGs correlates with longevity in CMS wheat plants compared to its fertile plants - Vimal Kumar Semwal; Bhupinder Singh; Renu Khanna-Chopra (Physiology and Molecular Biology of Plants, 2014)

Preparation of char from lotus seed biomass and the exploration of its dye removal capacity through batch and column adsorption studies - S. Nethaji; A. Sivasamy; R. Vimal Kumar; A. B. Mandal (Environmental Science and Pollution Research, 2013)

Study of atmospheric stagnation, recirculation and ventilation potential at Narora Atomic Power Station NPP site - Deepak Kumar; Avinash Kumar; Vimal Kumar; Jaivender Kumar; P. M Ravi (Environmental Monitoring and Assessment, 2013)

Leucaena leucocephala: an underutilized plant for pulp and paper production - Vimal Chandra Pandey; Akhilesh Kumar (Genetic Resources and Crop Evolution, 2013)

Traditional uses of medicinal plants for dermatological healthcare management practices by the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Anant Gopal Singh; Divya Darshan Tewari (Genetic Resources and Crop Evolution, 2013)

Documentation and determination of consensus about phytotherapeutic veterinary practices among the Tharu tribal community of Uttar Pradesh, India - Akhilesh Kumar; Vimal Chandra Pandey; Divya Darshan Tewari (Tropical Animal Health and Production, 2012)

Superoxide dismutase and ascorbate peroxidase are constitutively more thermotolerant than other antioxidant enzymes in Chenopodium album - Renu Khanna-Chopra; Vimal Kumar Semwal (Physiology and Molecular Biology of Plants, 2011)

Molecular characterization of Cucumber mosaic virus infecting Gladiolus, revealing its phylogeny distinct from the Indian isolate and alike the Fny strain of CMV - Vimal Kumar Dubey; Aminuddin; Vijai Pal Singh (Virus Genes, 2010)

Electrocoagulation Studies on Treatment of Biodigester Effluent using Aluminum Electrodes - F. Infant Anto Ponselvan; Mayank Kumar; Jodha Ram Malviya; Vimal Chandra Srivastava; Indra Deo Mall (Water, Air, & Soil Pollution, 2009)

Hydrographic characterization of southeast Arabian Sea during the wane of southwest monsoon and spring intermonsoon - K. G. Vimal Kumar; P. K. Dinesh Kumar; B. R. Smitha; H. Habeeb Rahman; Jacob Josia; K. R. Muraleedharan; V. N. Sanjeevan; C. T. Achuthankutty (Environmental Monitoring and Assessment, 2008)

Biodegradation and Decolorization of Pulp and Paper Mill Effluent by Anaerobic and Aerobic Microorganisms in a Sequential Bioreactor - Yogita Chuphal; Vimal Kumar; Indu Shekhar Thakur (World Journal of Microbiology and Biotechnology, 2005)

Improvedin vitro culture methodology in sugarcane by introducingAzospirillum sp andGluconacetobacter sp - S. P. Anand Kumar; V. P. Sobhakumari; P. Loganathan; M. Vimal Venkatesh (Sugar Tech, 2004)